ANALISIS PRODUK ROLLADE AYAM TERHADAP DAYA TERIMA KONSUMEN DAN MASA SIMPAN - Yulianti, Yeni; Maemunah, Yati Setiati (Jurnal Pendidikan Teknik dan Vokasional, 2021)
The research was to analyzed the effect of chicken rolade product with the addition of vegetables to consumer acceptance and shelf life in terms of organoleptic test on color, aroma, taste and texture aspects. Furthermore, the test of the shelf life of the product. Based on the color aspect most liked the addition of carrots with a percentage of 70% with a value of 4.1. Furthermore, the taste aspect most liked the addition of carrots with a percentage of 50% with a value of 4.17. Then the aroma aspect most liked the addition of carrots with the percentage of 50% and 60% with a value of 3.9. And the texture aspect most liked the addition of carrots with a percentage of 60% with a value of 4.17. The result of variance analysis on the length of rolled storage with the addition of carrot shows that the storage time has significant effect (α = 0.05) to the increase of rollade water content. The value of F arithmetic for the source of the old variance of storage is 157.1 and the value of F table 4.76. F count> F table, then reject H0, it means that storage period has an effect on rollade water content with 50%, 60% and 70% carrot addition. Keywords: analysis, chicken rolade, acceptance of consumers, shelf life